A comprehensive review of the roles of T-cell immunity in preeclampsia - Peng, Xu; Chinwe Oluchi-Amaka, Ibeh; Kwak-Kim, Joanne; Yang, Xiuhua (Frontiers in Immunology, 2025)
Preeclampsia (PE) is an obstetrical disorder that occurs after the 20th week of gestation. It is recognized as one of the “Great Obstetrical Syndromes” and principally contributes to maternal morbidity and mortality. PE has been associated with a range of immune disorders, including a preponderance of T helper (Th) 1 over Th2 cells and imbalanced levels of Th17 and T regulatory cells (Tregs). During pregnancy, T cells safeguard the placenta against immune rejection and aid embryo implantation while involved in pregnancy complications, such as PE. Promoting alloantigen-specific Treg cells is a potential preventive and therapeutic strategy for PE. However, ensuring the safety of mothers and infants is of the utmost importance since the risk-benefit ratio of reproductive and obstetric conditions differs significantly from that of immune diseases that pose a life-threatening risk. In this review, we systematically summarize the roles of T-cell immunity in the peripheral blood, reproductive tissues, and at the maternal-fetal interface of PE patients. Furthermore, the recent therapeutic approaches centered on targeting T cell immunity in PE are critically appraised.